Thermal effect on permeability in a single granite fracture: Experiment and theoretical model. (July 2020) - Peng, Huan; Zhao, Zhihong; Chen, Wei; Chen, Yuedu; Fang, Jun; Li, Bo
Abstract: The behavior of fluid flow through rock fractures at varying temperatures is a critical issue in many subsurface geo-energy projects. Previous work has considered the thermal effects on fracture permeability, but not in isolation of the chemical effects as well. Therefore, to quantitatively assess the mechanical influences on fracture permeability, we present results from permeability tests of five cylindrical Beishan granite samples, each with a single artificial fracture, at different temperatures. Three samples were tested at a constant confining pressure of 5 MPa and temperatures of 22 °C, 90 °C and 150 °C for 22 days, to examine creep-induced changes in fracture permeability. Fracture permeability decreases with time until about 10 days, and the eventual magnitudes of fracture permeability reduction are much greater at 90 °C and 150 °C than at 22 °C. Two samples were subjected to three heating cycles (30 °C to 150 °C) at a constant confining pressure of 5 MPa. Fracture permeability decreases as temperatures increase from 30 °C to 150 °C, and then slight changes in permeability occur as the sample is cooled to 30 °C. A similar tendency appears in subsequent temperature cycles, while the magnitude of fracture permeability reduction decreases with increasing heating-cooling cycles. A coupled thermal-mechanical model considering asperity damage is developed to describe the thermally-induced changes in fracture permeability, which properly predicts the experimental results. The residual deformation of asperities and temperature dependent Young's modulus play an important role in thermally-induced changes in fracture permeability.